Let a 1 , a 2 , … be an arithmetic progression and let b 1 , b 2 , … be a non-constant geometric progression .
We define the arithmetic-geometric progression c 1 , c 2 , … such that c k = a k ⋅ b k .
If c 1 = 1 , c 2 = 2 , and c 3 = 3 , what is the value of c 5 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great solution! Good job with finding the general term! Your notation was clear and consistent.
Some suggestions for improvements:
1. If you keep
a
b
=
1
and substitute this into the other
c
terms, this will be cleaner than dealing with the fraction
b
=
a
1
,
and then you will naturally get the quadratic equation without any
r
1
terms;
2. You could show in more detail why the general term is what you stated it to be.
Great solution! Good job with finding the general term! Your notation was clear and consistent.
Some suggestions for improvements:
1. If you keep
a
b
=
1
and substitute this into the other
c
terms, this will be cleaner than dealing with the fraction
b
=
a
1
,
and then you will naturally get the quadratic equation without any
r
1
terms;
2. You could show in more detail why the general term is what you stated it to be.
Problem Loading...
Note Loading...
Set Loading...
Suppose the common difference of a k is d and the common ratio of b k is r . Note that r = 0 , 1 . Also let's denote a 1 by a and b 1 by b . Note that a , b = 0 . We will write c 1 , c 2 , c 3 and c 5 in terms of a , b , d and r .
c 1 c 2 c 3 c 5 = a ⋅ b = 1 = ( a + d ) ⋅ b r = 2 = ( a + 2 d ) ⋅ b r 2 = 3 = ( a + 4 d ) ⋅ b r 4 = ?
Let's use the c 1 equation to eliminate b . ( b = a 1 ) .
c 2 c 3 c 5 = ( 1 + a d ) ⋅ r = 2 = ( 1 + a 2 d ) ⋅ r 2 = 3 = ( 1 + a 4 d ) ⋅ r 4 = ?
From the c 2 equation, we can use the relation a d = r 2 − 1 in the c 3 equation.
c 3 = ( 1 + r 4 − 2 ) ⋅ r 2 = 3
We get a quadratic equation in r .
− r 2 + 4 r = 3 ⟹ r 2 − 4 r + 3 = 0 ⟹ ( r − 1 ) ( r − 3 ) = 0
We know that r = 1 since b k is a non-constant geometric progression. Hence r = 3 . We also get a d = 3 2 − 1 = − 3 1 . We substitute these values in the equation of c 5 :
c 5 = ( 1 + 3 4 × ( − 1 ) ) ⋅ 3 4 = 3 − 1 × 3 4 = − 2 7 □
Just for fun, we shall attempt to find out the general term of c k .
We have obtained that a = 3 and d = − 1 . Thus, using the formula for arithmetic progressions a n = a + ( n − 1 ) d , we can say that the arithmetic progression a k = 3 + ( k − 1 ) ( 1 ) = 4 − k
Similarly, we have also obtained A = 3 1 , r = 3 . Geometric progressions can be represented as a n = a × r n − 1 . Thus the geometric progression b k = 3 1 × 3 k − 1 = 3 k − 2 .
We can write the general term c k as a k ⋅ b k = ( 4 − k ) ⋅ 3 k − 2